Chaperones and Catalysts: How Antigen Presentation Pathways Cope With Biological Necessity - Margulies, David H.; Taylor, Daniel K.; Jiang, Jiansheng; Boyd, Lisa F.; Ahmad, Javeed; Mage, Michael G.; Natarajan, Kannan (Frontiers in Immunology, 2022)
Immune recognition by T lymphocytes and natural killer (NK) cells is in large part dependent on the identification of cell surface MHC molecules bearing peptides generated from either endogenous (MHC I) or exogenous (MHC II) dependent pathways. This review focuses on MHC I molecules that coordinately fold to bind self or foreign peptides for such surface display. P¬¬eptide loading occurs in an antigen presentation pathway that includes either the multimolecular peptide loading complex (PLC) or a single chain chaperone/catalyst, TAP binding protein, related, TAPBPR, that mimics a key component of the PLC, tapasin. Recent structural and dynamic studies of TAPBPR reveal details of its function and reflect on mechanisms common to tapasin. Regions of structural conservation among species suggest that TAPBPR and tapasin have evolved to satisfy functional complexities demanded by the enormous polymorphism of MHC I molecules. Recent studies suggest that these two chaperone/catalysts exploit structural flexibility and dynamics to stabilize MHC molecules and facilitate peptide loading.